Events and children’s sense of time: a perspective on the origins of everyday time-keeping - Forman, Helen (Frontiers in Psychology, 2015)
In this article I discuss abstract or pure time versus the content of time, (i.e. events, activities, and other goings-on). Or, more specifically, the utility of these two sorts of time in time-keeping or temporal organization. It is often assumed that abstract, uniform and objective time is a universal physical entity out there, which humans may perceive of. However, this sort of evenly flowing time was only recently introduced to the human community, together with the mechanical clock. Before the introduction of mechanical clock-time, there were only events available to denote the extent of time. Events defined time, unlike the way time may define events in our present day culture. It is therefore conceivable that our primeval or natural mode of time-keeping involves the perception, estimation, and coordination of events. I find it likely that events continues to subserve our sense of time and time-keeping efforts, especially for children who have not yet mastered the use of clock-time. Instead of seeing events as a distraction to our perception of time, I suggest that our experience and understanding of time emerges from our perception of events.